Wine place research: Getting value from terroir and provenance in premium wine value chain interventions. Issue 4 (29th August 2019) - Warman, Russell D.; Lewis, Gemma K.
Abstract : Purpose: Place is an important aspect of wine quality, contributing both distinct sensory characteristics and symbolic significance to the consumer's experience, particularly in premium wine markets. The concepts of provenance and terroir, and the processes they describe, communicate meaning and significance along the value chain from wine production to consumption. This paper aims to clarify how these concepts are defined, how they contribute to premium wine value chains and how a greater understanding of these concepts by wine science researchers, and other actors, can enhance consumer value. Design/methodology/approach: To address these aims, a conceptual framework is developed, which outlines the conditions needed to fulfil the wine/place experience through the value chain. This framework resulted from discussions within a team of researchers currently undertaking a large project into place distinctiveness in Pinot Noir wines in Australia. The refinement and exploration of the concept is grounded in a multidisciplinary literature review. Findings: Through application of the framework, wine science researchers are advised to develop a knowledge co-production approach with other actors in the value chain. Doing so enables all actors to use evidence-based storytelling to enhance the role that place has in premium wine value and consumer experience. Originality/value: Overall, this paper contributes to the conversation surrounding the value of terroir and provenance, particularly as they relate to premium wine in New World wine regions. The innovative framework is applicable for both business and wine science researchers, especially those with decision-making responsibility and associated with wine science research institutions, funding bodies, industry partnerships and consortia.